2022
DOI: 10.3390/su14159353
|View full text |Cite
|
Sign up to set email alerts
|

On the Properties Evolution of Eco-Material Dedicated to Manufacturing Artificial Reef via 3D Printing: Long-Term Interactions of Cementitious Materials in the Marine Environment

Abstract: This paper deals with the evolution monitoring of biomass colonization and mechanical properties of 3D printed eco-materials/mortars immersed in the sea. Measurements of tensile strength, compressive strength, and Young’s modulus were determined on samples deployed along the Atlantic coast of Europe, in France, United Kingdom, Spain, and Portugal. The samples were manufactured using 3D printing, where six mix designs with a low environmental impact binder were used. These mortars were based on geopolymer and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Favorable early colonization was observed in concretes containing limestone and granite aggregates (Natanzi et al, 2021). Limestone and glass sand (0-0.3 mm) used as a substitute for 30% sand also showed good mechanical concrete properties to construct artificial reefs (Boukhelf et al, 2022), with better bio-colonization response observed after two years in glass sand concrete than limestone concrete. Crushed glass sand from broken car windshields, used as recycled fine aggregate to partially replace limestone sand in cement mortars, showed high environmental acceptability as artificial reef material while concrete containing shells showed the highest toxic effect (Santos et al, 2023).…”
Section: Different Types Of Concrete Ingredients For the Construction...mentioning
confidence: 96%
See 1 more Smart Citation
“…Favorable early colonization was observed in concretes containing limestone and granite aggregates (Natanzi et al, 2021). Limestone and glass sand (0-0.3 mm) used as a substitute for 30% sand also showed good mechanical concrete properties to construct artificial reefs (Boukhelf et al, 2022), with better bio-colonization response observed after two years in glass sand concrete than limestone concrete. Crushed glass sand from broken car windshields, used as recycled fine aggregate to partially replace limestone sand in cement mortars, showed high environmental acceptability as artificial reef material while concrete containing shells showed the highest toxic effect (Santos et al, 2023).…”
Section: Different Types Of Concrete Ingredients For the Construction...mentioning
confidence: 96%
“…The most investigated cements in the literature are CEM III (slag cements), of which some advantages have already been presented in section 2. These are: (1) increase durability of concrete due to its microstructure after hydration (Boukhelf et al, 2022), (2) increase early biological colonization of concrete due to its lower alkalinity compared to Portland cement (Natanzi et al, 2021), which provides a better substrate for attachment and growth of marine organisms (Rupasinghe et al, 2024), (3) fulfill inert landfill limits in ecotoxicological analysis, from which CEM III/B 32.5 N-SR is recommended for use in artificial reefs (Santos et al, 2023), (4) contain statistically lower amounts of metal released in controlled leaching experiments compared to concrete containing pulverized fly ash or Portland cement (McManus et al, 2018).…”
Section: Different Types Of Concrete Ingredients For the Construction...mentioning
confidence: 99%
“…The influence of the content of the activator in relation to the binder and the proportion of water to the binder were investigated. The best strength characteristics were obtained at a water-to-binder proportion of 0.33 and an activator amount of 8% of the binder volume [ 191 ]. The addition of GGBS to geopolymer concrete based on FA showed an improvement in its microstructure and strength but had almost no effect on the deformability of the material [ 192 ].…”
Section: Modern Trends and Innovations In The Field Of Research Of Ge...mentioning
confidence: 99%
“…It is not feasible to exclude this component from the mixture. Common binders like polymers and resins may harm marine life, but recent studies have developed bio-friendly binders (Ahn et al , 2021; Boukhelf et al , 2022; Salari et al , 2022) aimed at reducing environmental impact in marine applications such as ARs. BJ has been used to build ARs using marine-safe materials such as cement, mineral composites, sand or clays (Boskalis, 2017).…”
Section: Introductionmentioning
confidence: 99%